Implementasi Mekanisme Sleep - Wake Pada Node Sensor Berbasis GSM - Prasetyo Rizqi Santoso; Sabriansyah Rizqika Akbar; Eko Sakti Pramukantoro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The progress of the times in Indonesia in various sectors needs to be developed in a better direction. As there is a change in the monitor system on a land or the surrounding environment in order to save time checking the land and the environment, in addition it also requires a Sensor Node that can save power when monitoring a sector or environment, namely by sending to Could web ThingSpeak server that is useful for monitoring in real time and efficiently. In addition, a system is also needed along with sensor nodes that can make power savings. This time the sensor node is used in the form of light intensity, temperature sensor, and soil moisture sensor, where each sensor has a role to play in taking data on land or the environment. To send data to Cloud ThingSpeak, the GSM800L V2 module is used as a communication medium. In this study, energy saving methods using the mechanism (low power) are used or can also be called Sleep-Wake on Sensor Node. Testing on the system is done 7 times to determine the sleep and wake system and as many as 10 times for testing SIM800L V2. In this study the average results of testing the power saving (low power) and the tried wake as much as 7 times were 100.41mA for wake and 15.45mA for saving sleep power. The power saving is estimated at 84.6%. But sometimes this system is still constrained by the conditions of the place and the weather because SIM800L uses 2G networks.